(untitled) (European Journal of Marketing and Economics, 2022)
This exploratory investigation aims to develop a managerial decision model that assist international firms and investors in selecting the right valuable foreign country for their international operations. Two comparative and rich-information case studies were purposefully selected from among Arabian large firms. Additionally, six international investment decisions were investigated within these two cases and data were collected by in-depth interviews, follow-up interviews and questionnaire instrument. Within and cross-case analyses were undertaken in the current investigation. The findings demonstrated that a methodical and international experience-based strategic decision-making process was adopted to attain a profitable foreign country choice. The decision process comprised five critical managerial phases, that is, (1) analysis of internationalization drivers, (2) searching and development of location determinants and country alternatives, (3) obtaining adequate and related-information about potential countries, and, ultimately, assessment for these alternatives, (4) selection of a final beneficial foreign country choice, and, finally, (5) effective implementation of the selected country choice. The research findings provide theoretical and practical implications to the internationalization of firms as well as international investment. Further, it provides significant methodological contributions to international business research in relation to an effective multiple case study approach to capture elements of the international market selection process.